Identification of Functional Group Compound in Nginang Process: Ethnochemistry-Based Teaching Module for High School - Firmansyah, Dodiy; Siahaan, Jacksoon; Supriadi, Supriadi; Ariani, Sunniarti; Adiguna, Sya'ban Putra (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The Nginang process is one of the Sasak tribe's cultures that can be integrated into sasambo ethnochemical learning. The basic ingredients of the betel chewing process consist of betel leaves, lime, and areca nuts. These ingredients contain organic compounds that are identified as including hydroxyl (-OH) and carbonyl (C=O) groups. This study seeks to identify the functional groups present in betel leaves, areca nuts and residues after the betel chewing process in the functional group area and fingerprint area. The identification of organic compounds in this study was conducted through three stages: (1) grinding the